2020
DOI: 10.1111/cas.14716
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological significance of N‐myc downstream‐regulated gene 2 in cancer development through protein phosphatase 2A phosphorylation regulation

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…NDRG2 mediated the interaction between GSK3β and protein phosphatase 2A (PP2A), inducing the dephosphorylation of GSK3β at S9 by PP2A [70]. The interaction between NDRG2 and PP2A also activated PTEN, inhibiting AKT activation associated with cell survival and tumorigenesis [15,77]. Therefore, this shows that NDRG2 expression regulates pro/antiapoptotic protein levels, increasing the sensitivity of tumor cells to anticancer drugs (Figure 3).…”
Section: Sensitivity To Anticancer Drugs and Ndrg2mentioning
confidence: 99%
“…NDRG2 mediated the interaction between GSK3β and protein phosphatase 2A (PP2A), inducing the dephosphorylation of GSK3β at S9 by PP2A [70]. The interaction between NDRG2 and PP2A also activated PTEN, inhibiting AKT activation associated with cell survival and tumorigenesis [15,77]. Therefore, this shows that NDRG2 expression regulates pro/antiapoptotic protein levels, increasing the sensitivity of tumor cells to anticancer drugs (Figure 3).…”
Section: Sensitivity To Anticancer Drugs and Ndrg2mentioning
confidence: 99%
“…1 We previously reported that the aberrant activation of several signal transduction pathways in HTLV-1-infected T cells plays an important role in the development of HTLV-1-associated diseases. [2][3][4][5] Moreover, the constitutive activation of the JAK/STAT signaling pathway is involved in the progression and development of ATL-and HTLV-1-infected diseases. Although the molecular mechanism of the activated JAK/STAT signaling pathway has not yet been completely elucidated in ATL, the persistent phosphorylation of JAK1, JAK2, and JAK3 through the autocrine pathways of IL-2/IL-2R and the collapse of the dephosphorylation system lead to the subsequent entry of phosphorylated STAT1, STAT3, and STAT5 into the nucleus, resulting in the upregulation of downstream target genes that are involved in processes such as cell proliferation (Cyclin D), inhibition of apoptosis (Bcl-2, Bcl-xL), and inflammation (IL-1β, IL-6, and IFNγ).…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that the aberrant activation of several signal transduction pathways in HTLV‐1‐infected T cells plays an important role in the development of HTLV‐1‐associated diseases 2–5 . Moreover, the constitutive activation of the JAK/STAT signaling pathway is involved in the progression and development of ATL‐ and HTLV‐1‐infected diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In adult T-cell leukemia (ATL), PP2A has been reported to negatively regulate PRMT5 through the dephosphorylation of S355. This interaction is mediated by N-MYC downstream regulated gene (NDRG2), which acts as an adaptor between PRMT5 and PP2A ( 120 , 121 ). When NDRG2 expression is low, PRMT5 is reported to promote cell growth and prevent apoptosis ( 120 ).…”
Section: Interplay Of Pp2a and Chromatin Remodeling Complexesmentioning
confidence: 99%